2021
DOI: 10.1111/1471-0528.16690
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal tobacco smoke exposure and neurological impairment at 10 years of age among children born extremely preterm: a prospective cohort

Abstract: Objective To determine the association between prenatal tobacco smoke exposure and neurological impairment at 10 years of age among children born extremely preterm (<28 weeks of gestation). Design The Extremely Low Gestational Age Newborn (ELGAN) Study, a prospective cohort. Setting Ten‐year follow‐up of extremely preterm infants born at 14 US hospitals between 2002 and 2004. Methods Prenatal tobacco smoke exposure was defined as a mother’s report at enrolment of active (i.e. maternal) and passive smoking duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Motor disorders in the context of histological chorioamnionitis have been described in very preterm infants 37. Moreover, maternal smoking was more frequent in this category, and its association with neurodevelopmental anomalies has already been reported 38…”
Section: Discussionmentioning
confidence: 97%
“…Motor disorders in the context of histological chorioamnionitis have been described in very preterm infants 37. Moreover, maternal smoking was more frequent in this category, and its association with neurodevelopmental anomalies has already been reported 38…”
Section: Discussionmentioning
confidence: 97%
“…Prenatal tobacco smoke exposure was defined at the time of enrollment based on maternal self-report of active smoking during pregnancy. 53 Women were interviewed in their native language using a structured data questionnaire that included the question: “Did you smoke cigarettes during this pregnancy ( , )?” 53 …”
Section: Methodsmentioning
confidence: 99%
“…Prenatal maternal passive and active tobacco smoke exposure was ascertained by maternal interview at the time of participant enrollment ( Venkatesh et al, 2021 ). In this analysis, active maternal smoke exposure during pregnancy was assessed.…”
Section: Methodsmentioning
confidence: 99%
“…Our group has also previously reported that maternal overweight status or obesity was associated with increased ADHD behaviors at age 10, but the previously reported analysis did not control for family history of ADHD and did not assess the added effect of maternal diabetes ( van der Burg et al, 2017 ). A previous report on the effect of prenatal tobacco exposure on neurological outcomes identified that active, but not passive, smoking was associated with an increased risk of epilepsy ( Venkatesh et al, 2021 ). There was no effect on the risk of cerebral palsy or cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%